Application of Taguchi method in the optimization of process parameters for a sol–gel-derived nano-alumina film. (April 2016) - Mohan, Sreejith; Sivapirakasam, SP; Santhosh Kumar, MC; Surianarayanan, M
In this study, the Taguchi method is used to find the optimal process parameter combinations for realizing both lower film thickness and crystallite size and higher film thickness and crystallite size in a nano-alumina film prepared by sol–gel route. The process parameters evaluated were the molar concentration of the sol, dipping time, and sintering temperature. An orthogonal array, signal-to-noise ratio, and an analysis of variance were employed to analyze the effect of these process parameters. Surface profile measurement and X-ray diffraction techniques were used to measure the film thickness and crystallite size respectively. The analysis showed that the molar concentration of the sol was the most significant parameter on the film thickness and crystallite size, followed by dipping time and sintering temperature. Experimental results are supplied to exemplify the strength of this approach.